Why did Indonesia's Foreign Policy Stop IGGI? - Atep Abdurofiq; Gilang Rizki Aji Putra; Nur Rohim Yunus (BULETIN ADALAH, 2024)
Indonesia's Foreign Policy has played an essential role in determining the direction of this country's international relations. One example is the termination of Indonesia's participation in the Inter-Governmental Group on Indonesia (IGGI) in 1992. This study analyses the factors underlying Indonesia's foreign policy decision to terminate the IGGI. Using a historical approach and foreign policy analysis, this research highlights the political, economic and strategic factors influencing these policies. The results show that Indonesia's termination of the IGGI was a response to regional and global political dynamics at the time and shifts in Indonesia's foreign policy priorities. The implications of terminating the IGGI on Indonesia's bilateral relations with donor countries and Indonesia's domestic political dynamics are also debated in this analysis. This study provides important insights into the relationship between Indonesian foreign policy and regional political dynamics in the past and its relevance in the current context of Indonesian foreign policy.